Il sorpasso - Ortolani, Riziero 1926-2014 (The Criterion collection, 2014)
"The ultimate Italian road comedy, 'Il sorpasso' stars the unlikely pair of Vittorio Gassman and Jean-Louis Trintignant as, respectively, a waggish, freewheeling bachelor and the straitlaced law student he takes on a madcap trip from Rome to Tuscany. An unpredictable journey that careers from slapstick to tragedy, this film, directed by Dino Risi, is a wildly entertaining commentary on the pleasures and consequences of the good life. A holy grail of commedia all’italiana, 'Il sorpasso' is so fresh and exciting that one can easily see why it has long been adored in Italy." [criterion.com]
Original: Italien 1962
Bildformat 1.85:1 (16:9)
Two-DVD special edition features: new 4K digital restoration ; new introduction by filmmaker Alexander Payne ; new interviews with screenwriter Ettore Scola and film scholar Rémi Fournier Lanzoni ; interview from 2004 with director Dino Risi, conducted by film critic Jean A. Gili ; introduction by actor Jean-Louis Trintignant from a 1983 french television broadcast of the film "A Beautiful Vacation" ; a 2006 documentary on Risi featuring interviews with the director and his collaborators and friends ; excerpts from a 2012 documentary that returns to Castiglioncello, the location for the film’s beach scenes ; "Speaking with Gassman", a 2005 documentary on the relationship between actor Vittorio Gassman and Risi, directed by Risi’s son Marco ; trailer ; new english subtitle translation ; plus an essay by critic Phillip Lopate
Keywords: Film; DVD-Video